Tools for Information to Flow Securely and Swift-ly. - Wallach, Dan (Communications of the ACM, 2009)
The article discusses another article in the issue entitled "Building Secure Web Applications with Automatic Partitioning." The topic of the article is a computer programming tool called "Swift" built to provide a general-purpose programming language meant to build partitioned Web applications. Also discussed is Swift's ability to handle annotations which handle integrity constraints on data.